EFL Learners’ Levels of Classroom Performance Anxieties and Their causes in Classroom Speaking Activities in Afghanistan - Zia, Ziaurahman; Norrihan, Sulan (IJEE, 2015)
Studies conducted on language anxiety have found that foreign language anxiety (FLA) is an affecting variable in language learning. There is a negative correlation between foreign language anxiety and learners achievements (Aida, 1994; Horwitz, 2001; MacIntyre and Gardner, 1991). Besides, in foreign language learning situations, speaking is one of the most anxiety-provoking skill among other language learning skills which affects EFL learners’ language learning achievements the most (Chang, Horwitz & Shallert,1999). This study aims to examine English as foreign language learners’ speaking anxiety in language classrooms by measuring learners’ levels of classroom performance anxieties (Communication Apprehension, Test Anxiety and Fear of Negative Evaluation). It also determines the reasons which cause foreign language speaking anxiety in language learners inside language classroom. The participants of the study are 115 first year EFL undergraduates from one university in Afghanistan. The adapted version of (Horwitz, et al., 1986) Foreign Language Classroom Anxiety Scale (FLCAS) is used for data collection in the study. The results suggested that learners’ suffer from high level of all three types of performance anxieties. Fear of negative evaluation was the highest one which causes speaking anxiety in learners. Other sources that cause classroom speaking anxiety in learners are also discussed.